Localization of Cooperative WSN using Distributed PSO with Optimum References - Ravichander Janapati; Ch. Balaswamy; K. Soundararajan (Institute of Advanced Engineering and Science, 2016)
In indoor environment WSN nodes are deployed randomly and do not know the accurate position. Find the node position with the help of anchor nodes is known as localization. CRB algorithm selects the best anchor nodes which gives high accuracy. In this paper distributed PSO algorithm with optimum selection of reference nodes using CRB is proposed to find accurate node position. The proposed method performs better in comparison with other algorithms like PSO, RLS, LMS and GPS in terms of position accuracy, latency and complexity.